Acute Liver Failure Requiring Liver Transplantation due to Acute Hepatitis A Virus Infection - Chencheng Xie; Jonathan M. Fenkel; Dina L. Halegoua-DeMarzio; Jesse M. Civan; Danielle M. Tholey; Steven K. Herrine; Manish Thapar; Manju Ambelil; Sanaa Arastu; Adam M. Frank; Ashesh P. Shah; Jamie M. Glorioso; et al. (Case Reports in Transplantation, 2021)
Introduction. Hepatitis A infection (HAV) is generally characterized by an acute icteric illness or may have a subclinical self-limited course, although rarely, can result in fulminant hepatitis and death. In 2019, the City of Philadelphia declared a public health emergency due to an HAV outbreak. We are reporting a series of four cases of acute liver failure (ALF) requiring liver transplantation (LT) due to acute HAV. Methods. Chart review and case descriptions of four patients with acute HAV-related ALF who were expeditiously evaluated, listed as Status 1A, and who underwent LT between August 2019 and October 2019 at Thomas Jefferson University Hospital. Results. All four patients presented with acute hepatocellular jaundice and had a positive HAV IgM, and all other causes of ALF were excluded. All four cases met the American Association for the Study of Liver Diseases (AASLD) criteria for ALF. Three of the four cases met King’s College Criteria of poor prognosis for nonacetaminophen-induced ALF. All four patients underwent successful LT and were discharged six to twelve days postoperatively. One patient died of disseminated Aspergillus infection five months after LT, while the others have had excellent clinical outcomes shown by one-year follow-ups. All four explants had remarkably similar histological changes, revealing acute hepatitis with massive necrosis accompanied by a prominent lymphoplasmacytic inflammatory infiltrate and bile ductular proliferation. Conclusion. Although rare, patients presenting with acute HAV need close monitoring as they may rapidly progress to ALF. Early referral to a transplant center afforded timely access to LT and yielded overall good one-year survival. Widespread HAV vaccination for high-risk individuals is an essential strategy for preventing disease and curbing such future outbreaks.